Integrating power control, error correction coding, and scheduling for a CDMA downlink system. - Yuming Lu
Transmitting multimedia data over a code-division multiple access (CDMA) channel presents a new set of challenges: data demands will sometimes exceed the system capacity, in which case the system must make the most efficient use of its limited resources. In this paper, we present our approach for unifying power control, variable forward error correction (VFEC), and scheduling for a downlink system by allocating the system resources. The resources we consider are: fixed bandwidth available for each user and the transmit power budget for each cell. Our objective is to maximize the overall system satisfaction, which we call ?system utility.? This objective is achieved by applying a distributed algorithm which divides the overall optimization problem into a hierarchy of three levels (system, cell, and user), with each performing independent and parallel optimizations. We perform simulation-based evaluation of the system performance with a simple cell structure and uniformly distributed users. The system is simulated using a specific utility function: the step function. Finally, several practical issues regarding the implementation are investigated
Keywords: CDMA downlink system; DS-CDMA.; Bandwidth; Cell structure; Code-division multiple access; Distributed algorithm; Error correction coding; Indoor wireless communication systems; Multimedia data transmission; Optimization problem; Power control; Scheduling; Simulation-based evaluation; Step function; System capacity; System performance; System resources allocation; System utility; Transmit power budget; Uniformly distributed users; Variable forward error correction